E-COMMERCE TO SUPPORT MARKETING IN ASRILOKA WONOSALAM - Maulana, Hendra; Alit, Ronggo; Aqidatun Nisa, Diana (Jurnal Mebis, 2023)
The internet is an electronic tool that can be used for various activities such as communications, research, business transactions and others. Internet technology connects thousands of computer networks individuals and organizations around the world that internet technology is so popular. As is the sophistication of computer technology, all limitations in facilities, distance and transaction time can be overcome with easy. With just a "click" customers can get the items they want, they can find out what they want as desired and can carry out transactions with anyone without being limited by time and distance. In supporting its effectiveness, these sites continue to update and improve their features so as to make it easier for sellers to advertise their products and services, such as easy to access via Android and Blackberry mobile smartphones. The convenience offered making more and more sellers want to become members to market their goods and services. In product or service marketing activities, the focus required by the seller is subsequent promotion determine the channel to use. Advertising on e-commerce site channels is certainly expected have a positive impact on sellers. Effective marketing channels will be able to provide benefits and positive impacts in achieving the goals of marketing activities themselves. Besides that allows for the cultivation of relationships between sellers and buyers to interact with each other sustainable.